Region of Factor IXa Protease Domain that Interacts with Factor VIIIa: Analysis of Select Hemophilia B Mutants - Bajaj, S. Paul (Thrombosis and Haemostasis, 1999)
The identification of coagulation factor IX as a substance required for blood coagulation was first established by Pavlovsky, who reported that a mixture of blood from two hemophiliacs clotted normally.1 Based on this discovery and subsequent observations,2 hemophilia was divided into two conditions-hemophilia A or factor VIII deficiency, the most prevalent condition, and hemophilia B or factor IX deficiency, a less common condition. Since then, much has been learned about the molecular and structural biology of factor IX. It is a vitamin K-dependent protein that participates in the middle phase of the intrinsic as well as the extrinsic coagulation cascade.3 The gene for factor IX consists of eight exons and seven introns, is approximately 34 kb long, and located on the long arm of the X-chromosome at band Xq27.1.4,5 The positions of the introns in the factor IX gene are essentially identical to those of the other three homologous proteins, namely, factor VII, factor X, and protein C;3 the genes for the latter three proteins, however, are not located on the X-chromosome.